Towards mission-driven investment in new antimicrobials? What role for Chinese strategic industrial financing vehicles in responding to the challenge of antimicrobial resistance? - Lewis Husain; Yajing Hu; Yangmu Huang (BMC, 2024)
Abstract Background Antimicrobial resistance (AMR) causes high levels of global mortality. There is a global need to develop new antimicrobials to replace those whose efficacy is being eroded, but limited incentive for companies to engage in R&D, and a limited pipeline of new drugs. There is a recognised need for policies in the form of 'push' and 'pull' incentives to support this R&D. This article discusses China, a country with a rapidly emerging pharmaceuticals and biotech (P&B) sector, and a history of using coordinated innovation and industrial policy for strategic and developmental ends. We investigate the extent to which 'government guidance funds' (GGFs), strategic industrial financing vehicles (a 'push' mechanism), support the development of antimicrobials as part of China's 'mission-driven' approach to innovation and industrial policy. GGFs are potentially globally significant, having raised approximately US$ 872 billion to 2020. Results GGFs have a substantial role in P&B, but almost no role in developing new antimicrobials, despite this being a priority in the country's AMR National Action Plan. There are multiple constraints on GGFs' ability to function as part of a mission-driven approach to innovation at present, linked to their business model and the absence of standard markets for antimicrobials (or other effective 'pull' mechanisms), their unclear 'social' mandate, and limited technical capacity. However, GGFs are highly responsive to changing policy demands and can be used strategically by government in response to changing needs. Conclusions Despite the very limited role of GGFs in developing new antimicrobials, their responsiveness to policy means they are likely to play a larger role as P&B becomes an increasingly important component of China's innovation and industrial strategy. However, for GGFs to effectively play that role, there is a need for reforms to their governance model, an increase in technical and managerial capacity, and supporting ('pull') incentives, particularly for pharmaceuticals such as antimicrobials for which there is strong social need, but a limited market. Given GGFs' scale and strategic importance, they deserve further research as China's P&B sector becomes increasingly globally important, and as the Chinese government commits to a larger role in global health.